J. S. Bach's 'Leipzig' Chorale Preludes: Music, Text, Theology - Leaver, Robin A. (Rowman & Littlefield Publishers, 2011)
In 2007, the great Bach scholar Anne Leahy died at the age of 46. She was a leading light in Bach studies and lecturer at the Dublin Institute of Technology (DIT) Conservatory of Music and Drama. Posthumously edited by renowned Bach scholar Robin A. Leaver, Leahy's dissertation research forms the basis for this original study of the preludes to Bach's Leipzig chorales. Originally composed in Weimar and later revised in Leipzig, Bach's compositions have been a source of some puzzlement. As Leahy notes, "the original intentions of Bach and the possible purpose of this collection might be regarded as speculative." Working from available sources, however, she argues that through the careful examination of the links among the music, hymn texts, and theological sources some answers may be had. From Bach's personal and deep interest in Lutheran theology to his enormous musical passion, Leahy considers closely a series of critical questions: does the original manuscript for the chorales simply reflect a random gathering of compositions or is there a common theme in setting? How critical is the order of the chorales and what is the theological significance of that order? Were the chorales a unified collection, and if so, which parts were to be included and which not? Indeed, were the chorales themselves part of a possibly larger corpus? As Leahy makes evident, there are no simple answers, which is why she considers critical the relationship the texts of the hymns to the chorales and to one another, outlining a theological pattern that is vital to fully grasping the guiding philosophy of these compositions. J. S. Bach's "Leipzig" Chorale Preludes: Music, Text, Theology is ideally suited for Bach scholars and those with a general interest in the intricate connections between text and music in the composition of religious music.